Evaluasi Pelaksanaan Discharge Planning pada Pasien Diabetes Melitus - Martini Martini; Erfina Erfina; Saldy Yusuf (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The aim of this review is to map the discharge planning implementation model and its effects. The research method uses a literature review by searching for appropriate articles in scientific databases, namely PubMed, EBSCO, ScienceDirect and Garuda using keywords based on the Population method: Diabetes mellitus; Concept: Discharge Planning and Context: Hospital. As a result of the research, after searching for articles, 44 articles were found that matched the research questions and resulted in 20 articles to be included in this review. Evaluation of the discharge planning implementation model used a research design of 7 RCT studies, 5 quasi-experimental studies, 3 cross-sectional studies, 2 retrospective studies, 1 qualitative study, 1 cohort study, and 1 comparative descriptive study. We identified several models for evaluating the implementation of discharge planning in DM patients. In conclusion, the evaluation model for implementing discharge planning in the form of training and education can increase knowledge and compliance with treatment as well as glycemic control. Keywords: Discharge Planning, DM Patients, Hospital